Applying Social Exchange Mechanism to Determine Proactive Behavior in Regional Development Banks - Sunardi Sunardi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This research has its purpose to analyze the effect of perceived organizational support (POS) and job satisfaction toward proactive behavior among employees who work in East Java regional development banks. A total of 92 senior officers participated in the study by filling out a complete online questionnaire which was distributed within one month. The collected primary data was then analyzed using path analysis techniques, as this technique aimed to test the direct effect of POS on proactive behavior and indirectly through job satisfaction. The finding reveals show that the effect of POS toward job satisfaction is found to be very large, indicating that POS is the most important determinant of job satisfaction. Meanwhile, compared to POS, job satisfaction has the greatest effect on proactive behavior. This shows that there is an important mediating role from job satisfaction on the effect of POS on proactive behavior. The greater the support felt by senior officers, the more satisfied they will be at work and tend to be more proactive at work. Social exchange theory can explain how proactive behavior can be displayed by individuals in an organization, but the results imply the need for further studies to explore more broadly other potential determinants of proactive behavior.